Population transition in South Asia - Bose, Ashish; Premi, Mahendra K. (Delhi B.R. Pub. Corp., 1992)
Contributed articles.
Includes bibliographical references.
Keywords: South Asia -- Population -- Congresses; South Asia -- Population policy -- Congresses